The effects of reinforcement magnitude on skill acquisition for children with autism. Issue 4 (17th August 2015) - Paden, Amber R.; Kodak, Tiffany
Abstract : We examined the effects of reinforcement magnitude on skill acquisition during discrete‐trial training. After conducting a magnitude preference assessment, we compared acquisition during conditions with large and small magnitudes of edible reinforcement to a praise‐only condition. Although all participants showed a preference for the large‐magnitude reinforcer, preference did not predict the magnitude that produced the fastest skill acquisition.